Two stroke small engine test rig design and its engine performance analysis - Rosman, Razali (2009)
This thesis is about how to perform an analysis of 30.5cc two stroke engine without using dynamometer. As we know, dynamometer is very expensive in the market and some way need to be build to perform engine performance analysis based on functionality of dynamometer. Hence, dynamometer been replaced with alternator where it is very cheap and easy to find in market. So, engine test rig had been designed before can proceed to fabrication process. Some sketches software had used like autocad and solidwork to draft out the shape of engine test rig. Materials selection also included in this designed process. Variable loads will be given at constant engine speed to see whether performance of engine will decrease or increase. Here, we can analyze at which engine speed is the optimum of performance from this small engine. So, some losses like power and fuel can be decrease.